2015
DOI: 10.1007/s00005-015-0367-5
|View full text |Cite|
|
Sign up to set email alerts
|

Studies on Immunogenicity and Antigenicity of Baculovirus-Expressed Binding Region of Plasmodium falciparum EBA-140 Merozoite Ligand

Abstract: The erythrocyte binding ligand 140 (EBA-140) is a member of the Plasmodium falciparum erythrocyte binding antigens (EBA) family, which are considered as prospective candidates for malaria vaccine development. EBA proteins were identified as important targets for naturally acquired inhibitory antibodies. Natural antibody response against EBA-140 ligand was found in individuals living in malaria-endemic areas. The EBA-140 ligand is a paralogue of the well-characterized P. falciparum EBA-175 protein. They both sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
(74 reference statements)
0
5
0
Order By: Relevance
“…16 The reorientation stage is thought to be mediated by merozoite ligands released from apical organelles to erythrocytes, including 2 ligand families, P falciparum reticulocyte-binding protein homologs (PfRhs) and erythrocyte-binding-like proteins. [17][18][19][20] Among those, 4 receptor-ligand pairs, glycophorin A-EBA175, 21 glycophorin C-EBA140, [22][23][24] complement receptor 1 (CR1)-PfRh4, 25 and CD147-PfRh5 11,26,27 are involved at this stage, of which the CD147-PfRh5 interaction is the only one that is essential for the parasite invasion. The TJ formation and motility involve 2 parasitesecreted proteins, P. falciparum apical membrane antigen (PfAMA1) and rhoptry neck protein 2 (RON2), to form an AMA1-RON2 complex.…”
Section: Introductionmentioning
confidence: 99%
“…16 The reorientation stage is thought to be mediated by merozoite ligands released from apical organelles to erythrocytes, including 2 ligand families, P falciparum reticulocyte-binding protein homologs (PfRhs) and erythrocyte-binding-like proteins. [17][18][19][20] Among those, 4 receptor-ligand pairs, glycophorin A-EBA175, 21 glycophorin C-EBA140, [22][23][24] complement receptor 1 (CR1)-PfRh4, 25 and CD147-PfRh5 11,26,27 are involved at this stage, of which the CD147-PfRh5 interaction is the only one that is essential for the parasite invasion. The TJ formation and motility involve 2 parasitesecreted proteins, P. falciparum apical membrane antigen (PfAMA1) and rhoptry neck protein 2 (RON2), to form an AMA1-RON2 complex.…”
Section: Introductionmentioning
confidence: 99%
“…The heat-denatured Region II was used as the negative binding control. The cells were washed three times with PBS and incubated for 1 h at 4 °C with rabbit serum (diluted 1:200) raised against the whole P. falciparum EBA-140 Region II [ 45 ]. The cells were washed three times with PBS and incubated for 45 min at 4 °C with FITC-conjugated swine anti-rabbit Ig antibody (DakoCytomation, Glostrup, Denmark) and analyzed for fluorescence intensity using flow cytometry (FACSCalibur, BD Biosciences, San Jose, USA).…”
Section: Methodsmentioning
confidence: 99%
“…As discussed above, there is a general agreement that GPC but not GPD is P. falciparum EBA-140 receptor on human RBCs [79, 8183, 97, 98]. However, evaluation of the binding of the homologous P. reichenowi EBA-140 ligand binding to chimpanzee RBCs [99] unexpectedly demonstrated that the chimpanzee homolog of human GPD is probably the receptor for that ligand [4, 100].…”
Section: Introductionmentioning
confidence: 99%